Karyotyping of green, yellow and red matoa (Pometia pinnata J.R.Forst. & G.Forst.) from Central Java, Indonesia - ENDANG YUNIASTUTI; ANANDA PUTRI DEWANTARI MASAILLA; NANDARIYAH NANDARIYAH; NAILU RAHMAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Yuniastuti E, Masailla APD, Nandariyah, Rahmah N. 2023. Karyotyping of green, yellow and red matoa (Pometia pinnata J.R.Forst. & G.Forst.) from Central Java, Indonesia. Biodiversitas 24: 40-46. Matoa (Pometia pinnata J.R.Forst. & G.Forst.) belongs to Sapindaceae family and is widely distributed naturally in Indonesia. However, research on matoa plants,especially for the genetic aspect is poorly reported. Genetic information, through chromosome analysis can be helpful in plant breeding programs. This study aimed to analyze karyotype of chromosomes green, yellow and red matoa collected from Central Java, Indonesia. Chromosome analysis in this study used the squash preparation method. This research was the first karyotyping of matoa using 3 types based on exocarp colors, namely green, yellow and red skin matoa. Each type of matoa was repeated 4 times. The results showed that three types of matoa skin colors have the same number of chromosomes, namely 2n=2x=22 with each chromosome size of green, yellow, and red matoa are 1.070±0.251 ?m, 1.025±0.281 ?m, 006±0.252 ?m, respectively and all of matoa have a metacentric chromosome’s form. The karyotype formula for each type of matoa is 2n=2x=22=11m.